A Gaussian Model for the Time Development of the Sars-Cov-2 Corona Pandemic Disease. Predictions for Germany Made on 30 March 2020 - Reinhard Schlickeiser; Frank Schlickeiser (Physics, 2020)
For Germany, it is predicted that the first wave of the corona pandemic disease reaches its maximum of new infections on 11 April 2020 <semantics> <mover> − 3.4 + 5.4 </mover> </semantics> days with 90% confidence. With a delay of about 7 days the maximum demand on breathing machines in hospitals occurs on 18 April 2020 <semantics> <mover> − 3.4 + 5.4 </mover> </semantics> days. The first pandemic wave ends in Germany end of May 2020. The predictions are based on the assumption of a Gaussian time evolution well justified by the central limit theorem of statistics. The width and the maximum time and thus the duration of this Gaussian distribution are determined from a statistical <semantics> χ 2 </semantics> -fit to the observed doubling times before 28 March 2020.